RELATIONSHIP BETWEEN MACROECONOMIC VARIABLES VOLATILITY AND STOCK MARKET VOLATILITY IN INDONESIA - LOKE, PHUI SEA (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The aim of this study is to examine the relationship between macroeconomic variables volatility and stock market volatility in Indonesia. There are four macroeconomic variables selected, including industrial production, exchange rate, inflation rate and money supply in this paper. The stock market and macroeconomic variables are carried out from January 1986 to December 2013 which contains a monthly data set of 336 observations. Data of all the variables are obtained from the DataStream. This paper employs GARCH (1, 1) model to estimate the conditional volatility. The results showed all variables exhibit volatility clustering. Based on VAR Granger Causality test, the result indicates that there is only an unidirectional causal relationship from stock market volatility to exchange rate volatility in the short run. In addition from the multiple regression analysis, exchange rate volatility is found to be significant with stock market volatility. However, the findings concluded that there is a weak relationship between macroeconomic variables volatility and stock market volatility in Indonesia. Policy makers should take into account the stock market volatility in making any policy related to exchange rate and vice versa.